Influence of Brazilian Jiu-Jitsu Belt Graduations on the Performance of Elite Female Combat Athletes - Brito, C (Sciendo, 2024)
Introduction. In Brazilian Jiu-jitsu (BJJ), match durations are determined by belt rank according to the rules. However, a detailed understanding of the dynamics in female matches across belt levels is lacking. Gaining this insight could refine training, better meeting the needs of female athletes at each progression stage. Therefore, this study aims to conduct a comparative time-motion analysis of combat phases among elite female practitioners across different belt ranks. Material and Methods. The sample was composed of White (n = 60), Blue (n = 150), Purple (n = 108), Brown (n = 56), and Black (n = 48) belts. All combats were analyzed using a BJJ time-motion protocol according to the sequential actions of the combats (i.e., approach, gripping, attack, defense, transition, guard, mount, side control, low-intensity movements, and total time), p ≤ 0.05. Results. The main results indicated longer time in the black belt division vs. white and blue belts in low-intensity movements [170(63;311.6) s vs. 75.1(39.7; 201.9)s, and 93.1 (34.2; 168.7)s], defensive actions [31(10.2;76.6)s vs. 12.2(50.5; 22.4)s, and 22.4(11; 49.4)s], and approach actions [9.1(5.5;23.3)s vs. 5.2(2.5; 9.9)s, and 4.8(1; 12)s], respectively. Conclusions. No effects were observed in combat-determining domain actions such as gripping, transition actions, side control, and mount, even with differences in the rules, suggesting a progressive reduction in intensity accompanying the increase in total combat time as the rank in BJJ increases. © 2024 Sciendo. All rights reserved.